2020
DOI: 10.1080/16878507.2020.1812798
|View full text |Cite
|
Sign up to set email alerts
|

Development of theoretical-computational model for radiation shielding

Abstract: Development of materials for radiation shielding application, which are lightweight, flexible, and robust increases in demand for nuclear radiation facilities including industrial or medical applications. In this paper, three metals (lead, gadolinium, bismuth) doped polymeric compounds (poly-acrylonitrile, polyethylene, and kevlar) were simulated by using theoretical and computational model. It was assumed that lead, gadolinium and bismuth were dispersed homogenously. Both theoretical and computational model w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…It is clear that we have first developed polymer fibers filled with as high as 50 wt % BC and 70 wt % PWO particles for smooth weaving of fabrics. It is believed that whether neutron absorption or γ-ray shielding requires much more loadings of functional particles in polymers for desirable radiation shielding. , Actually, it is at the expense of mechanical properties and then loss of usability. That is, the fabrics from the highly filled polymer fillers in this work guarantee much more excellent radiation shielding.…”
Section: Resultsmentioning
confidence: 99%
“…It is clear that we have first developed polymer fibers filled with as high as 50 wt % BC and 70 wt % PWO particles for smooth weaving of fabrics. It is believed that whether neutron absorption or γ-ray shielding requires much more loadings of functional particles in polymers for desirable radiation shielding. , Actually, it is at the expense of mechanical properties and then loss of usability. That is, the fabrics from the highly filled polymer fillers in this work guarantee much more excellent radiation shielding.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure , the presence of a large number of functional particles in the densely stacked nonwoven fibers ensures effective radiation protection, while the presence of curved channels between the fibers also meets the air permeability requirements . In relation to extensive research on employing nonwoven membranes for X-ray shielding, such as WO 3 , Bi 2 O 3 , and W, it is noteworthy that the filling rate of functional fillers in polymers remains relatively low. According to the traditional radiation shielding theory, the size and filling amount of functional particles play a crucial role in improving the radiation protection ability of composite materials. This implies that meeting the criteria for effective shielding against high-energy γ-rays becomes challenging when the filling is low. Consequently, highly filled polymer nonwoven membranes are regarded as potential contenders for manufacturing PPE with significant promise.…”
Section: Introductionmentioning
confidence: 99%
“…41 42 and their results indicated that gamma-ray absorption properties of nylon 1,1 were better than other investigated samples. 22 Gamma ray radiation shielding properties of hydrogel composites by combining an acrylamide polymer with clay containing PbO 2 nanoparticles were calculated by Park et al 23 Mass attenuation coefficient of some polymers which are poly-propylene, perspex, bakelite, teflon, polyethylene, polycarbonate, nylon 6-6, and PMMA in the energy range 59.5-1332.5 keV were calculated using simulation and theoretical by Vahabi et al 24 Mechanical and gammaray absorption properties of materials included poly-ether-ether-ketone as a substrate and containing distinct tungsten contents were examined by Wu et al 25 Their results showed that radiation absorption properties of higher tungsten containing material were higher and radiation shielding properties depend on the thickness of the material. 25 Our interest arouses that polymers are used in dosimetry and medical application for tissue counterparts due to their chemical and physical features.…”
mentioning
confidence: 99%